An evolutionary analysis of the assignment of property rights - Atsushi Tsuneki (Osaka University, Institute of Social and Economic Research (ISER), 2017)
We develop an evolutionary game model to reveal the theoretical basis for the assignment of property right, where both plaintiff and defendant argue for their rights by claiming their reliance investment.We allow for the possibility that the value of the total product depend not only on the investment conferred by the owner but also on the reliance investment provided by the trespasser. The resulting evolutionary stable set of preferences shows that the endowment effect hardwired to the ownersand trespassersdepends on the difference of productivities among both parties and the density of owners within the population.
Keywords: C73; K11; 330; Evolutionary Game; Property Right; Reliance Investment; Endowment Effect